Manufacturing technology, optical and spectral properties of nano-structurized thin ZnO films - Panasyuk, M.R.; Turko, B.I.; Kapustianik, V.B.; Lubochkova, G.A.; Rudyk, V.P.; Vas`kiv, A.P.; Davydov, V.M. (Functional Materials, 2005)
Dependence of cathodoluminescence parameters on the annealing temperature and RF ion etching has been studied for nano-structurized thin zinc oxide films obtained by RF magnetron reactive sputtering. The film structure has been characterized by X-ray diffraction. Thermal annealing and RF ion etching have been found to increase the cathodoluminescence intensity, mainly due to enlargement of the nanocrystallite mean size. Дослiджено залежнiсть параметрiв катодолюмiнесценцii наноструктурованих тонких плiвок оксиду цинку, отриманих методом ВЧ-магнетронного реактивного розпилення, вiд температури вiдпалу та обробки методом ВЧ-iонного травлення. Методом рентгено-структурного аналiзу дослiджено структуру плiвок. Встановлено, що термiчний вiдпал та ВЧ-iонне травлення забезпечують пiдсилення iнтенсивностi катодолюмiнесценцii, насамперед за рахунок зростання середнiх розмiрiв нанокристалiтiв. Исследована зависимость параметров катодолюминесценции наноструктурированных тонких пленок оксида цинка, полученных методом ВЧ-магнетронного реактивного распыления, от температуры отжига и обработки ВЧ-ионным травлением. Методом рентгеноструктурного анализа исследована структура пленок. Установлено, что термический отжиг и ВЧ-ионное травление обеспечивают усиление интенсивности катодолюминесценции, главным образом, за счет увеличения средних размеров кристаллитов.